Insights Into Immunothrombotic Mechanisms in Acute Stroke due to Vaccine-Induced Immune Thrombotic Thrombocytopenia - de Buhr, Nicole; Baumann, Tristan; Werlein, Christopher; Fingerhut, Leonie; Imker, Rabea; Meurer, Marita; Götz, Friedrich; Bronzlik, Paul; Kühnel, Mark P.; Jonigk, Danny D.; Ernst, Johanna; Leotescu, Andrei; et al. (Frontiers in Immunology, 2022)
During the COVID-19 pandemic, vaccination is the most important countermeasure. Pharmacovigilance concerns however emerged with very rare, but potentially disastrous thrombotic complications following vaccination with ChAdOx1. Platelet factor-4 antibody mediated vaccine-induced immune thrombotic thrombocytopenia (VITT) was described as an underlying mechanism of these thrombotic events. Recent work moreover suggests that mechanisms of immunothrombosis including neutrophil extracellular trap (NET) formation might be critical for thrombogenesis during VITT. In this study, we investigated blood and thrombus specimens of a female patient who suffered severe stroke due to VITT after vaccination with ChAdOx1 in comparison to 13 control stroke patients with similar clinical characteristics. We analyzed cerebral thrombi using histological examination, staining of complement factors, NET-markers, DNase and LL-37. In blood samples at the hyper-acute phase of stroke and 7 days later, we determined cell-free DNA, myeloperoxidase-histone complexes, DNase activity, myeloperoxidase activity, LL-37 and inflammatory cytokines. NET markers were identified in thrombi of all patients. Interestingly, the thrombus of the VITT-patient exclusively revealed complement factors and high amounts of DNase and LL-37. High DNase activity was also measured in blood, implying a disturbed NET-regulation. Furthermore, serum of the VITT-patient inhibited reactive oxygen species-dependent NET-release by phorbol-myristate-acetate to a lesser degree compared to controls, indicating either less efficient NET-inhibition or enhanced NET-induction in the blood of the VITT-patient. Additionally, the changes in specific cytokines over time were emphasized in the VITT-patient as well. In conclusion, insufficient resolution of NETs, e.g. by endogenous DNases or protection of NETs against degradation by embedded factors like the antimicrobial peptide LL-37 might thus be an important factor in the pathology of VITT besides increased NET-formation. On the basis of our findings, we discuss the potential implications of the mechanisms of disturbed NETs-degradation for diagnostic and therapeutic approaches in VITT-related thrombogenesis, other auto-immune disorders and beyond.